The Diary of a Young Girl - Frank, Anne, 1929-1945 (Mumbai, India A Wilco Book, 2008)
In the summer of 1942, fleeing the horrors of the Nazi occupation, Anne Frank and her family were forced into hiding in the back of an Amsterdam warehouse. Aged thirteen when she went into the secret annexe, Anne kept a diary in which she confided her innermost thoughts and feelings, movingly revealing how the eight people living under these extraordinary conditions coped with the daily threat of discovery and death, being cut off from the outside world, petty misunderstandings and the unbearable strain of living like prisoners. An intimate record of tension and struggle, adolescence and confinement, anger and heartbreak, this is the definitive edition of the diary of Anne Frank.
Keywords: Jews -- Frank, Anne, 1929-1945 -- Holocaust, Jewish--(1939-1945)